Day 1 Mon, May 02, 2016 2016
DOI: 10.4043/27141-ms
|View full text |Cite
|
Sign up to set email alerts
|

Investigations into the Fatigue Strength of CRA Lined Pipe

Abstract: Pipes that experience sour service need to resist that corrosive environment. One method for achieving corrosion resistance is by lining the inside of the pipe with a corrosion resistant alloy (CRA), such as stainless steel or a nickel based alloy. This has the advantage of being much cheaper than either making the pipe from the CRA or metallurgically bonding CRA to the pipe (ie clad pipe). Lined pipe is gaining popularity, and has so far been used successfully in applications where applied strain levels are l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…Furthermore, fatigue life of the alloy 625 liner is higher than that of the alloy 316L liner. This is in line with other studies, where it has been shown that crack initiation and growth is slower in alloy 625 than in alloy 316L [22].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, fatigue life of the alloy 625 liner is higher than that of the alloy 316L liner. This is in line with other studies, where it has been shown that crack initiation and growth is slower in alloy 625 than in alloy 316L [22].…”
Section: Resultssupporting
confidence: 93%
“…Eighteen dumbbell specimens, six for each pipe size, are fatigue tested at a frequency of 2 Hz to determine the fatigue endurance of MLPs with imperfect liners. Although the maximum service temperature can be high (100-150 • C or above), testing is conveniently undertaken at room temperature as fatigue cracks generally grow slower at elevated temperature [22].…”
Section: Small Scale Fatigue Testsmentioning
confidence: 99%
“…Weld overlay is a fusion-based welding process for depositing coats, allowing manufacturing clad pipes with various thicknesses, diameters, and lengths [8]. Besides, weld overlay is employed to seal the liner at the pipe ends and joint preparation of lined pipes [9,10]. TIG hotwire is often used for cladding critical parts of subsea equipment because it presents high efficiency, low heat input, and high quality [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Reelability of MLPs has been the subject of numerous studies over the past decades [17][18][19][20][21][22][23][24][25][26]. It was shown that when an MLP is subjected to bending the liner initially ovalizes together with the backing pipe [27,28].…”
Section: Introductionmentioning
confidence: 99%